P.003 Differences between younger and older dementia patients at a rural and remote memory clinic. (5th June 2019) - Wong, J; Kirk, A; Perlett, L; Karunanayake, C; Morgan, D; O'Connell, ME
Abstract : Background: Young-onset dementia (YOD) patients and their caregivers face unique challenges in diagnosis and management. We aimed to compare the characteristics of rural YOD and late-onset dementia (LOD) patients.Methods: A total of 333 consecutive patients (YOD=61, LOD=272) at a rural and remote memory clinic between March 2004 and July 2016 were included in this study. Each patient had neuropsychological assessment. Health, mood, function, behaviour, and social factors were also measured. Both groups were compared using χ2 tests and independent sample tests.Results: YOD patients were more likely to be married, employed, current smokers, and highly educated. They reported fewer cognitive symptoms, but had more depressive symptoms. YOD patients were less likely to live alone and use homecare services. YOD caregivers were also more likely to be a spouse and had higher levels of distress than LOD caregivers.Conclusions: Our findings indicate YOD and LOD patients have distinct characteristics and services must be modified to better meet YOD patient needs. In particular, the use of homecare services and caregiver support may alleviate the higher levels of distress found in YOD patients and their caregivers. Additional research should be directed to addressing YOD patient depression, caregiver distress, and barriers to services.